Biocontrol potential of wine yeasts against four grape phytopathogenic fungi disclosed by time-course monitoring of inhibitory activities - Esteves, Marcos; Lage, Patrícia; Sousa, João; Centeno, Filipe; de Fátima Teixeira, Maria; Tenreiro, Rogério; Mendes-Ferreira, Ana (Frontiers in Microbiology, 2023)
Grapes’ infection by phytopathogenic fungi may often lead to rot and impair the quality and safety of the final product. Due to the concerns associated with the extensive use of chemicals to control these fungi, including their toxicity for environment and human health, bio-based products are being highly preferred, as eco-friendlier and safer alternatives. Specifically, yeasts have shown to possess antagonistic activity against fungi, being promising for the formulation of new biocontrol products.In this work 397 wine yeasts, isolated from Portuguese wine regions, were studied for their biocontrol potential against common grapes phytopathogenic fungal genera: Aspergillus, Botrytis, Mucor and Penicillium. This set comprised strains affiliated to 32 species distributed among 20 genera. Time-course monitoring of mold growth was performed to assess the inhibitory activity resulting from either diffusible or volatile compounds produced by each yeast strain. All yeasts displayed antagonistic activity against at least one of the mold targets. Mucor was the most affected being strongly inhibited by 68% of the tested strains, followed by Botrytis (20%), Aspergillus (19%) and Penicillium (7%). More notably, the approach used allowed the detection of a wide array of yeast-induced mold response profiles encompassing, besides the decrease of mold growth, the inhibition or delay of spore germination and the complete arrest of mycelial extension, and even its stimulation at different phases. Each factor considered (taxonomic affiliation, mode of action and fungal target) as well as their interactions significantly affected the antagonistic activity of the yeast isolates. The highest inhibitions were mediated by volatile compounds. Total inhibition of Penicillium was achieved by a strain of Metschnikowia pulcherrima, while the best performing yeasts against Mucor, Aspergillus and Botrytis, belong to Lachancea thermotolerans, Hanseniaspora uvarum and Starmerella bacillaris, respectively. Notwithstanding the wide diversity of yeasts tested, only three strains were found to possess a broad spectrum of antagonistic activity, displaying strong or very strong inhibition against the four fungal targets tested. Our results confirm the potential of wine yeasts as biocontrol agents, while highlighting the need for the establishment of fit-for-purpose selection programs depending on the mold target, the timing, and the mode of application.